And Miles to Go Before We Sleep: EAST Diversity and Inclusivity Progress and Remaining Challenges. Issue 4 (11th April 2023) - Tseng, Esther S.; Weaver, Jessica L.; Sangosanya, Ayodele T.; Gelbard, Rondi B.; Martin, Matthew J.; Tung, Lily; Santos, Ariel P.; McCunn, Maureen; Bonne, Stephanie; Joseph, Bellal; Zakrison, Tanya L.; ,
Abstract : Objective: The aim of this study was to examine the diversity, equity, and inclusion landscape in academic trauma surgery and the EAST organization. Summary Background Data: In 2019, the Eastern Association for the Surgery of Trauma (EAST) surveyed its members on equity and inclusion in the #EAST4ALL survey and assessed leadership representation. We hypothesized that women and surgeons of color (SOC) are underrepresented as EAST members and leaders. Methods: Survey responses were analyzed post-hoc for representation of females and SOC in academic appointments and leadership, EAST committees, and the EAST board, and compared to the overall respondent cohort. EAST membership and board demographics were compared to demographic data from the Association of American Medical Colleges. Results: Of 306 respondents, 37.4% identified as female and 23.5% as SOC. There were no significant differences in female and SOC representation in academic appointments and EAST committees compared to their male and white counterparts. In academic leadership, females were underrepresented ( P < 0.0001), whereas SOC were not ( P = 0.08). Both females and SOC were underrepresented in EAST board membership ( P = 0.002 and P = 0.043, respectively). Of EAST's 33 presidents, 3 have been white women (9%), 2 have been Black, non-African American men (6%), and 28 (85%) have been white men. When compared to 2017 AAMC data, women are well-represented in EAST's 2020 membership ( P < 0.0001) and proportionally represented on EAST's 2019-2020 board ( P > 0.05). Conclusions: The #EAST4ALL survey suggests that women and SOC may be underrepresented as leaders in academic trauma surgery. However, lack of high-quality demographic data makes evaluating representation of structurally marginalized groups challenging. National trauma organizations should elicit data from their members to re-assess and promote the diversity landscape in trauma surgery.